Pensamiento social italiano sobre América Latina. - Tedeschi, Stefano; Surian, Alessio (CLACSO, 2017)
Cultural relations between Italy and Latin America have a long tradition throughout the 20th century: journalists, travelers and politicians wrote and reflected on that distant continent, which had suddenly become familiar thanks to the experience of mass migration. From this long migratory tradition and a solid tradition of Hispanic studies, in the second half of the 20th century a notable school of Americanists was formed in the fields of history, social thought, anthropology, literary studies and cultural, which produced a large number of studies whose value has been internationally recognized, and which since the 1960s has not ceased to be a point of reference.